Thinking styles as predictors of psychological readiness of students for innovative activities - Elena A. Suroedova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper deals with the problem of thinking styles and creativity as predictors of students psychological readiness for innovation. The aim of the study was to identify the influence of students thinking styles on their psychological readiness for innovation. The study involved 100 students of the Don State Technical University, aged from 17 to 27 years. The research methods were the survey method, statistical analysis methods (descriptive statistics, multiple regression analysis (step-by-step)). The following methods were used as psychodiagnostic tools: the questionnaire Psychological readiness for innovation (V.E. Klochko, O.M. Krasnoryadtseva); the method of measuring the style of thinking (A.K. Belousova); the method of determining the type of thinking of J. Bruner in the modification of G.V. Rezapkina; the questionnaire Styles of thinking (R. Bramson, A. Harrison, adapted by A. Alekseev, L. Gromova). The study found that students psychological readiness for innovation is influenced by thinking styles and creativity. Predictors of psychological readiness for innovation are creativity, realistic and critical thinking styles. The preference for activities that require innovation is influenced by creativity, initiative, idealistic and realistic thinking styles. Predictors of readiness for change are creativity and critical thinking styles. The practical significance of the research lies in the possibility of applying in the educational process the knowledge about the influence of students thinking styles and creativity on their psychological readiness for innovation.